Building the Prestige in the rural sociology Anthropology study for Al-Baaji villages in Salah Aldin - شبيب محمد علي, صالح (Al-Adab Journal, 2018)
It poses this research anthropological study was based approach cognitive tools anthropological depends mostly on observation, interview and informants, has been focused axis of research on the nature of the social status and a link to this status physical considerations and considerations of the moral, and the reflection of this link to change many of the cultural patterns and the system of control and regulation. Us a large area of ​​alteration made in the Iraqi countryside showed after entering the technology and the impact of the changes taking place in Iraq post-2003 political and religious reflection on the overall social forms. As it began to be formed on the basis of lifestyle and material profit, and began to lose many of the rural accepted concepts in anthropological studies, or otherwise, the contents of these forms, clan, traditional authority and the family began to change with the compressor and control factors.There is no longer a central position in the Head of the countryside, meet around the secondary potentialities associated and dependent, but the place has become an individual based on the nature of the work or the dimension of the source of the decision and power.